2020
DOI: 10.3390/ijerph17030677
|View full text |Cite
|
Sign up to set email alerts
|

Perceptions of the Use of Alcohol and Drugs after Sudden Bereavement by Unnatural Causes: Analysis of Online Qualitative Data

Abstract: Bereavement is associated with an increased risk of psychiatric morbidity and all-cause mortality, particularly in younger people and after unnatural deaths. Substance misuse is implicated but little research has investigated patterns of drug or alcohol use after bereavement. We used a national online survey to collect qualitative data describing whether and how substance use changes after sudden bereavement. We conducted thematic analysis of free-text responses to a question probing use of alcohol and drugs a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
14
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(20 citation statements)
references
References 45 publications
2
14
1
Order By: Relevance
“…In relation to other qualitative research, our own thematic analyses of these data specifically for people bereaved by suicide (Eng et al, 2019), and non-suicide unnatural deaths (Drabwell et al, 2020), identified that for both groups struggles over control with alcohol or drugs were prominent and many used substances for specific ends. For those bereaved by non-suicide unnatural causes these ends included gaining a release, escaping reality, and achieving emotional openness (Drabwell et al, 2020). For those bereaved by suicide, they included coping with overwhelming emotions, and honoring the memory of the deceased (Eng et al, 2019).…”
Section: Results In the Context Of Other Studiesmentioning
confidence: 96%
See 2 more Smart Citations
“…In relation to other qualitative research, our own thematic analyses of these data specifically for people bereaved by suicide (Eng et al, 2019), and non-suicide unnatural deaths (Drabwell et al, 2020), identified that for both groups struggles over control with alcohol or drugs were prominent and many used substances for specific ends. For those bereaved by non-suicide unnatural causes these ends included gaining a release, escaping reality, and achieving emotional openness (Drabwell et al, 2020). For those bereaved by suicide, they included coping with overwhelming emotions, and honoring the memory of the deceased (Eng et al, 2019).…”
Section: Results In the Context Of Other Studiesmentioning
confidence: 96%
“…drove efforts to control their use (Eng et al, 2019;Drabwell et al, 2020). A thematic analysis of interviews with 57 young British men aged 19-35 who had been bereaved by non-suicide unnatural causes found many similar themes (Creighton et al, 2015).…”
Section: Results In the Context Of Other Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Drabwell et al [34] analyzed alcohol consumption after sudden bereavement by unnatural causes among adults aged 18 to 40. Their results show how men use alcohol to facilitate the expression of emotions, while in young people it was more common as a form of rebellion.…”
Section: Manuscripts Selected By Usmentioning
confidence: 99%
“…Some studies point to intensified alcohol use in grieving situations 30 . Thus, as COVID-19 emerges as one of the main causes of death, there is additional concern about alcohol consumption patterns during isolation and in the coming years.…”
mentioning
confidence: 99%